Dampak Berkurangnya Jenis Pupuk Bersubsidi terhadap Produksi dan Pendapatan Petani Padi Sawah (Studi Kasus di Desa Limpoccoe, Kecamatan Cenrana, Kabupaten Maros, Provinsi Sulawesi Selatan) - Srimeliani; Bakri, Rasyidah; Rukka, Rusli M.; Nadja, Rahmawati A.; Diansari, Pipi (Program Studi Agribisnis INSTIPER Yogyakarta, 2025)
Rice plants are one of the food crop commodities that have an important meaning for the people of Indonesia. This is because the product produced from rice, namely rice, is one of the staple foods of the Indonesian people. In dealing with the increasing demand for rice, farmers can take various actions depending on local conditions, available resources, and local government policies. One of the factors that affects farmers' production costs is the cost of fertilizer. The government provides a fertilizer subsidy program to farmers to support the agricultural sector. The provision of subsidized fertilizers aims to improve the welfare of farmers. Amendments to the Regulation of the Minister of Agriculture Number 49 of 2020, subsidized fertilizers are Urea, ZA, NPK, SP36, and Organic fertilizers, then changed to the Regulation of the Minister of Agriculture Number 10 of 2022, subsidized fertilizers are only Urea and NPK (Nitrogen, Phosphate, and Potassium) fertilizers. This study aims to identify the impacts caused by the reduction in subsidized fertilizer types on the production and income of rice farmers in Limpoccoe Village, Cenrana District, Maros Regency, South Sulawesi Province and to identify efforts made by farmers in anticipating fertilizer needs after the reduction in subsidized fertilizer types. This study was conducted using an independent sample t-test. The location of the study was in Limpoccoe Village, Cenrana District, Maros Regency, South Sulawesi Province. Respondents in this study numbered 57 people who were taken based on a random sampling method from a population of 587 rice farmers. The test results showed that there was no significant difference in the production and income of rice farmers in Limpoccoe Village, Cenrana District, Maros Regency, South Sulawesi Province after the reduction in subsidized fertilizer types. Rice farmers in Limpoccoe Village, Cenrana District, Maros Regency, South Sulawesi Province predominantly reduced fertilizer doses after the reduction in subsidized fertilizer types and some maintained their habits.